Acute effects of two different stretching methods on local muscular endurance performance - Gomes, T. M.; Simão, R.; Marques, M. C.; Costa, P. B.; da Silva, N. J. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to assess the acute effects of the static and proprioceptive neuromuscular facilitation (PNF) stretching methods on local muscular endurance performance at intensities between 40 and 80% of 1 repetition maximum (1RM) for the knee extension (KE) and bench press (BP) exercises. Fifteen male volunteers (23.9 ± 4.3 years; 174.5 ± 8.5 cm; and 77.8 ± 7.6 kg), who were nonathletes but had previous experience in resistance training, volunteered for this study. Participants were assigned to 9 randomly ordered experimental conditions, in which all subjects performed endurance tests at 40, 60, and 80% of 1RM, preceded by static stretching (SS), PNF, and no stretching (NS) in the KE and BP exercises. One-way repeated-measures analysis of variance (NS × SS × PNF) revealed an influence of stretching for all intensities only when the PNF treatment was used. Significant differences (p < 0.05) were found in the KE exercise, with reductions in the number of repetitions when comparing PNF40 (23.7 ± 2.7) to NS40 (27.5 ± 3.6); PNF60 (12.6 ± 2.8) to SS60 (16.5 ± 4.1) and NS60 (17.3 ± 3.2); and PNF80 (6.3 ± 1.7) to SS80 (9.9 ± 2.5) and NS80 (9.8 ± 2.3) conditions. Significant differences (p < 0.05) were also found for the BP exercise with decreases in the number of repetitions when comparing PNF60 (13.7 ± 2.8) to NS60 (17.0 ± 3.0) and PNF80 (6.2 ± 2.2) to NS80 (8.7 ± 2.3) conditions. These findings suggest that for the intensities studied (40, 60, and 80% 1RM), only the PNF method decreased muscle endurance. Strength and conditioning professionals may want to consider avoiding PNF stretching before activities requiring local muscular endurance performance.